Health Risk Factors Among Miners, Oil and Gas Extraction Workers, Other Manual Labor Workers, and Nonmanual Labor Workers, BRFSS 2013–2017, 32 States. (August 2020) - Yeoman, Kristin; Sussell, Aaron; Retzer, Kyla; Poplin, Gerald
Background : Analyzing health risk factors among current workers by industry and occupation (IO) provides information on disparities between worker groups, especially when comparing workers within manual labor occupations. Mining and oil and gas extraction (OGE) are unique industries with different work environments that could affect health risk factors. The study objective was to compare the prevalence of health risk factors of miners, OGE, other manual labor, and nonmanual labor workers. Methods : The Behavioral Risk Factor Surveillance System's IO module was analyzed for years 2013–2017 to compare prevalences of excessive alcohol use, smoking, smokeless tobacco use, seat belt use, inadequate sleep, and obesity among four worker groups. National Health Interview Survey IO codes were used to categorize miners, OGE, other manual labor, and nonmanual labor workers. Findings : Miners and OGE workers had higher prevalence estimates than both nonmanual and manual labor workers for all health risk factors except current smoking. Both miners and OGE workers were significantly more likely than other manual labor workers to report smokeless tobacco use and not always wearing seatbelts. Compared with other manual labor workers, OGE workers were significantly more likely to report obesity, and miners were significantly more likely to report inadequate sleep. Conclusion/Application to Practice : Prevalence of most health risk factors differed among miners, OGE, other manual labor, and nonmanual labor workers. These differences could lead to disparities in health outcomes. Occupational health professionals in mining and OGE can use this information to inform and target integrated wellness and health and safety programs.